Latin lover - Comencini, Cristina 1956-; Lisi, Virna 1936-2014; Finocchiaro, Angela; Finocchiaro, Angela; Bruni Tedeschi, Valeria 1964- (01 distribution, 2015)
The five daughters of a famous actor, all from different mothers and different nationalities, get together on the 10th anniversary of his death for a celebration of his career. --IMDb
Aspect ratio: 16:9 2.40:1
Keywords: Film; DVD-Video